Lipoabdominoplasty complications: an update - Carranza, Vianney Anguiano (International Surgery Journal, 2025)
Lipoabdominoplasty, which combines abdominoplasty with liposuction, has become a widely accepted technique for abdominal contouring. Although it carries a risk of complications, its overall safety profile is favorable compared to traditional abdominoplasty when performed with proper patient selection and technique. A review of the literature was conducted to summarize the most common complications associated with lipoabdominoplasty and outline evidence-based management strategies. The most frequently reported complications include seroma (6.5-8.8%), wound infection, minor dehiscence, hypertrophic scarring (up to 30% in post-bariatric patients), and fat necrosis. Major events such as full-thickness flap necrosis, deep venous thrombosis, and necrotizing fasciitis are rare but potentially life-threatening. Risk factors include elevated BMI, smoking, diabetes, and advanced age. Preventive techniques-such as preservation of Scarpa’s fascia, progressive tension sutures, and careful hemostasis-reduce the incidence of seroma and wound complications. Management strategies include aspiration or drainage for seroma, culture-directed antibiotics for infection, and surgical debridement for necrotizing fasciitis when indicated. Lipoabdominoplasty is a safe and effective procedure when performed by experienced surgeons with careful patient optimization. Complications are generally minor and manageable with early recognition and targeted treatment. Adherence to refined surgical principles and evidence-based preventive measures minimizes morbidity and ensures optimal functional and aesthetic outcomes.